Spiritual solutions : answers to life's greatest challenges - Chopra, Deepak (Harmony Books, 2012)
Demonstrates how to navigate life challenges in four common areas including relationships, success, health, and personal growth, providing compassionate recommendations for achieving balance and handling conflicts.